2022
DOI: 10.1002/mnfr.202200098
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Infant Fecal Fermentation Characteristics of Human Milk Oligosaccharides Were Controlled by Initial Microbiota Composition More than Chemical Structure

Abstract: Scope Human milk oligosaccharides (HMOs), multifunctional glycans naturally present in human milk, are known to contribute to the infant's microbiota and immune system development. However, the molecular specificity of HMOs on microbiota and associated fermentation is not yet fully understood, and is important for the development of infant formula optimum functionality. Methods and results In vitro fermentation is carried out on structurally different HMOs with infant fecal inocula dominated by Bifidobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Within HMOs, sialylated HMOs exhibited the highest acid production capability, while neutral fucosylated HMOs and FOSs demonstrated comparable acid production levels. Interestingly, GOSs in the positive control generated the least acid, deviating from findings in previous studies [1,52]. Furthermore, our study, employing B. infantis-dominant and B. breve-dominant strains as inocula, demonstrated varying levels of AA production by Bifidobacteria during HMO degradation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Within HMOs, sialylated HMOs exhibited the highest acid production capability, while neutral fucosylated HMOs and FOSs demonstrated comparable acid production levels. Interestingly, GOSs in the positive control generated the least acid, deviating from findings in previous studies [1,52]. Furthermore, our study, employing B. infantis-dominant and B. breve-dominant strains as inocula, demonstrated varying levels of AA production by Bifidobacteria during HMO degradation.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, there was minimal production of PA and BA at the conclusion of fermentation. Conversely, in a separate study using Bacteroides -dominated inocula, PA and BA were generated in the later phases of fermentation [ 52 ]. This discrepancy may stem from distinct HMO utilization strategies employed by Bifidobacterium and Bacteroides .…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate, produced upon fermentation of HMOs ( 30 ), is well known for its interactions with, e.g., colonocytes and small intestine epithelial cells. This interaction occurs via binding to GPR41 and GPR43, or butyrate becomes intracellularly available via MCT-mediated transport and can act as HDAC inhibitor or suppress NF-κB activation ( 20 , 24 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although human milk contains butyrate at physiologically relevant levels (median concentration of 0.75 mM, depending on, e.g., stage of lactation ( 34 )), the HMOs present in human milk are fermented by specific intestinal bacteria into SCFAs ( 30 ) and will therefore naturally be present together in the infant’s intestine. Here, we also observed that combined exposure of butyrate with 2’FL enhanced secretion of hallmark indicator of type 1 immunity IFNγ, and regulatory IL10 in IEC/DC/T cells on top of the 2’FL associated IL13 increase observed in T cells instructed by primed DC from 2’FL-IEC/DC cultures.…”
Section: Discussionmentioning
confidence: 99%
“…91 Nevertheless, these proportions of HG and RG-I in pectins varied depending on the source. For instance, apple pectins contained proportions of 53.00% of HG and 26.94% of RG-I, 94 while potato pectins exhibited a substantial proportion of RG-I region of 75.00% but a relatively low HG region of 20.00%. 95 The structural characteristics of kidney bean NSPs are highly influenced by the extraction and purification methods (Table 5).…”
Section: Structural Characteristics Of Kidney Bean Nspsmentioning
confidence: 99%